Knowledge and Self-Care Practices on Diabetic Foot among Diabetic Patients in Public Hospitals of Lahore, Pakistan - A Descriptive Study - Fatima Asim, Sumaira Sharif, Rozina Asghar, Ayesha Shahzadi, Aqsa Hafeez, Sobia Mehnaz (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The purpose of this study is to examine the degree of knowledge and practise of diabetic foot self-care among people with diabetes mellitus, as well as to determine the variables that influence the level of knowledge and practise in a public hospitals of Lahore, Pakistan. It is also beneficial for raising awareness about foot-care in diabetic patients. Methodology: A descriptive cross-sectional research was done in outpatient diabetes clinics on 153 adult patients with diabetes. Participants were given self-administered questionnaires about their knowledge and practise of diabetic foot self-care. Their responses were used to determine their scores. A total score of >60% was assessed as good and <40% as poor. SPSS was used for analyzing data frequency and percentages. Results: Amongst 153 patients majority of patients 85(55.5%) had poor knowledge about diabetic foot care, 48(31.3%) had average knowledge, and 20(13.2%) had good knowledge about foot care. About 79(51.6%) participants had poor practices regarding diabetic foot care, 49(32%) had satisfactory practices, and 25(16.4%) had good practices of diabetic foot care. Patients with college level education had good level of knowledge about foot care. Knowledge of participants and self-care practices is significantly associated with age and education of participants. Practical Implication: Knowledge and self-care practices of foot care were associated with age and education level of participants. Health-care professionals should concentrate on filling knowledge gaps in foot care, promoting good foot hygiene habits, and enticing patients to take part in diabetes education initiatives. Conclusion: The results of study concluded that majority of participants had poor knowledge and self-care practices about foot care. Keywords: Knowledge; Diabetic Foot; Diabetes Mellitus; Self-Care Practices